1998
DOI: 10.1007/bf03216748
|View full text |Cite
|
Sign up to set email alerts
|

A potent anti-diabetic agent fromKalopanax pictus

Abstract: To search for the anti-diabetic principle from the stem bark of Kalopanax pictus, seven kinds of chemical constituents including hedearagenin glycosides and phenolic glycosides were isolated. The anti-diabetic evaluation of these isolates in the streptozotocin-induced diabetic rats exhibited that kalopanaxsaponin A has a potent anti-diabetic activity in contrast to a mild activity of hedearagenin. In addition, significant hypocholesterolemic and hypolipidemic activities of kalopanaxsaponin A and hedearagenin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 13 publications
0
38
0
2
Order By: Relevance
“…15) Since 1996, we also have elucidated a potent hypoglycemic, 4) cytotoxic, 5) antimutagenic 5) and hepatotoxic 16) effects of hederagenin monodesmosides. Because the active component of this crude drug has never been reported on anti-inflammatory effect, we examined the effects of the various hederagenin monodesmodies on release of two inflammatory mediators (NO and PGE 2 ), TNF-a, and the expression level of iNOS and COX-2 of the macrophages activated by LPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15) Since 1996, we also have elucidated a potent hypoglycemic, 4) cytotoxic, 5) antimutagenic 5) and hepatotoxic 16) effects of hederagenin monodesmosides. Because the active component of this crude drug has never been reported on anti-inflammatory effect, we examined the effects of the various hederagenin monodesmodies on release of two inflammatory mediators (NO and PGE 2 ), TNF-a, and the expression level of iNOS and COX-2 of the macrophages activated by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous reports on anti-diabetic, 4) cytotoxic 5) and antifungal assays 6) have shown that the active components should be hederagenin monodesmosides. In addition, we also demonstrated that hederagenin bisdesmoside could be converted to its monodesmosides and its serial saponins by human intestinal bacteria and that these metabolites showed anti-diabetic activity.…”
mentioning
confidence: 99%
“…KPA and KPI reduced the vascular permeability, and KPA was more effective than KPI. When the biological activities of kalopanaxsaponins were investigated in hyperglycemia, 4,7) cytotoxicity, 5) mutagenicity, 13) and hepatotoxicity model, 14) KPA was found to be the most active compound. In this FCA-induced rat rheumatoid arthritis model, KPA was also effective.…”
Section: Time Course Of Metabolism Of Kpk and Kpj By Human Intestinalmentioning
confidence: 99%
“…1 Phytochemical studies on the stem bark have demonstrated the presence of hederagenin glycosides, syringin, liriodendrin, and coniferylaldehyde glucosides, 2,3 and the methanol extract of the stem bark of K. pictus has been reported to possess cytotoxic, 4 antidiabetic, 5 and anti-inflammatory activities. 6 In this report, a new compound (3) and 11 known compounds (1, 2 and 4-12) were isolated from the methanol extract of the stem bark of K. pictus.…”
mentioning
confidence: 99%